Diminished Responsibility Under Singapore Law (An Evaluation) - Cheang, Molly (Journal of Malaysian and Comparative Law, 2019)
The concept of diminished responsibility was introduced into English law by section 2(1) of the Homicide Act, 1957 which declares that a person shall not be guilty of murder if he "was suffering from such abnormality of mind (whether arising from a condition of arrested or retarded development of mind or any inherent causes or induced by disease or injury) as substantially impaired his mental responsibility for his acts and omissions in doing or being a party to the killing." as such, the defence of diminished responsibility reduces the crime from murder to manslaughter.